Transport of Tl(I) in water-saturated porous media: Role of carbonate, phosphate and macromolecular organic matter. (1st November 2020) - Wang, Hainan; Liu, Juchao; Yao, Jinni; He, Qiang; Ma, Jun; Chai, Hongxiang; Liu, Caihong; Hu, Xuebin; Chen, Yao; Zou, Yijie; Xiong, Jiaming; Huangfu, Xiaoliu
Highlights: Tl(I) transport in water-saturated porous media is explored. pH and IS could affect Tl(I) transport significantly. Both carbonate and phosphate acted as inhibitors for Tl(I) transport. HA-facilitated Tl(I) transport was associated with HA-Tl complxes and competing adsorption. BSA impeded Tl(I) mobility resulting from adsorption sites for Tl(I) by BSA deposition. Abstract: Understanding the transport behaviors of thallium (Tl) in porous media is of considerable interest for both natural soils and artificial filtration removal of Tl. In this context, the transport behaviors of Tl(I) in water-saturated sand columns under different conditions were systematically investigated. It was found that, in addition to the effects of pH and ionic strength (IS), the transport of Tl(I) depended on the carbonate, phosphate and macromolecular organic matter as well. Tl(I) broken the columns more difficultly under higher pH and lower IS conditions. Moreover, the adsorption of carbonate and phosphate on sand surfaces may increase the retention of Tl(I) in columns. As for macromolecular organic matter, humic acid (HA) facilitated Tl(I) transport, especially under neutral and alkaline conditions (7.0 and 9.8), which was possibly associated with Tl-complexes formation and competed adsorption between Tl(I) and HA. However, bovine serum albumin (BSA) impeded Tl(I) transport for the reason that deposited BSA might provide more adsorption sites for Tl(I), though Tl(I) had a slight effect on BSA transport. In order to evaluate the mechanisms of transport, a dual-sites non-equilibrium model was applied to fit the breakthrough curves of Tl(I). Retardation factor ( R ) values of individual Tl(I) transport from model calculations were found to be higher than that of Tl(I) transport with HA and lower than that of Tl(I) transport with BSA. The fraction of instantaneous sorption sites ( β ) was found to decrease with increasing pH, implying nonequilibrium sorption is a main sorption mechanism of Tl(I) with pH increasing. The fundamental data obtained herein demonstrated that carbonate, phosphate and macromolecular organic matter significantly influenced the Tl(I) migration and could lead to the leaking or bindings of Tl(I) at Tl-occurring sites. Graphical abstract: Image, graphical abstract